Complete Blood Count and saliva parameters as an indicator for infected patients with coronavirus covid-19 - Hussein, Sumaiah I; Abd, Suha T; AL-khayat, Fadia A; Mahmood, Heba k (Journal of Baghdad College of Dentistry, 2023)
Background: Coronavirus, which causes respiratory illness, has been a public health issue in recent decades. Because the clinical symptoms of infection are not always specific, it is difficult to expose all suspects to qualitative testing in order to confirm or rule out infection as a test. Methods: According to the scientific studies and investigations, seventy-three results of scientific articles and research  were obtained using PubMed, Medline, Research gate and Google Scholar. The research keywords used were COVID-19, coronavirus, blood parameters, and saliva. Results: This review provides a report on the changes in the blood and saliva tests of those who are infected with the COVID-19.COVID-19 is a systemic infection that has a substantial influence on the hematological system and hemostasis, thus deviations from normal levels of laboratory tests, including the blood and saliva test show that specific testing for detecting COVID-19 infection is required. Conclusions: The blood and saliva tests aid in the clinical monitoring of the patient's health.  It has advantages such as the following: it has non-invasive properties, low cost, and good stability, addition to minimum risk of infection transport.